From Divergence to Convergence: Reevaluating the History Behind China's Economic Boom - Brandt, Loren; Ma, Debin; Rawski, Thomas G. (Journal of Economic Literature, 2014)
China's long-term economic dynamics pose a formidable challenge to economic historians. The Qing Empire (1644–1911), the world's largest national economy before 1800, experienced a tripling of population during the seventeenth and eighteenth centuries with no signs of diminishing per capita income. While the timing remains in dispute, a vast gap emerged between newly rich industrial nations and China's lagging economy in the wake of the Industrial Revolution. Only with an unprecedented growth spurt beginning in the late 1970s did this great divergence separating China from the global leaders substantially diminish, allowing China to regain its former standing among the world's largest economies. This essay develops an integrated framework for understanding that entire history, including both the divergence and the recent convergent trend. We explain how deeply embedded political and economic institutions that contributed to a long process of extensive growth before 1800 subsequently prevented China from capturing the benefits associated with the Industrial Revolution. During the twentieth century, the gradual erosion of these historic constraints and of new obstacles erected by socialist planning eventually opened the door to China's current boom. Our analysis links China's recent development to important elements of its past, while using recent success to provide fresh perspectives on the critical obstacles undermining earlier modernization efforts, and their eventual removal. (JEL N15, N45, O11, O47, P21, P24, P26)